'Nothing Goes to Waste': A professional learning programme for early childhood centres. Issue 1 (March 2020) - Boyd, Wendy
Waste created by modern lifestyles is of key concern to sustainable development globally. Early childhood centres engage in sustainable practices, and waste management is one of these practices. Past research has indicated that early childhood staff are challenged to implement sustainable practices. However, the National Quality Standard requires centres to engage in sustainable practices. This study reports on research undertaken to examine the effectiveness of effectiveness of a waste management professional learning programme run in 30 early childhood centres in Australia. The data collected was interviews of the directors of 16 centres, 6 months after the programme. Findings found the programme to be effective in encouraging waste management practices as all centres changed practices to reduce or recycle waste. The majority of the centres had a staff member who championed environmental education and was an inspiration for other staff, but barriers to good waste management practices were experienced because of external stakeholders' power over decision-making, owners not agreeing to make changes, and, internally, from having to maintain hygienic standards. Recommendations are made for future professional learning programmes.